2017
DOI: 10.3389/fimmu.2017.00782
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NOD-Like Receptor Protein 3 Inflammasome Is Protective in Juvenile Influenza A Virus Infection

Abstract: Influenza A virus (IAV) is a significant cause of life-threatening lower respiratory tract infections in children. Antiviral therapy is the mainstay of treatment, but its effectiveness in this age group has been questioned. In addition, damage inflicted on the lungs by the immune response to the virus may be as important to the development of severe lung injury during IAV infection as the cytotoxic effects of the virus itself. A crucial step in the immune response to IAV is activation of the NOD-like receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Modulating the NLRP3 inflammasome activity can prove to be a promising strategy for the intervention of viral diseases. In a juvenile mouse model of IAV infection, MCC950, a specific inhibitor of the NLRP3 inflammasome, ameliorates severe NLRP3 inflammasome-mediated lung injury without impairing viral clearance (76).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Modulating the NLRP3 inflammasome activity can prove to be a promising strategy for the intervention of viral diseases. In a juvenile mouse model of IAV infection, MCC950, a specific inhibitor of the NLRP3 inflammasome, ameliorates severe NLRP3 inflammasome-mediated lung injury without impairing viral clearance (76).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Studies have shown that both NLRP3 and AIM2 are required for inflammation during influenza infection through the use of mice lacking components of NLRP3 and AIM2 (15,16). However, temporal inhibition of NLRP3 during influenza infection through the use of a small-molecule inhibitor of NLRP3 results in decreased disease and lung inflammation if used later in the course of infection (17,18). To investigate the individual component AIM2, we challenged WT and AIM2 -/mice with A/ PR/8/34 for 6 days followed by MSSA and saw enhanced bacterial clearance in the superinfected AIM2 -/mice compared with superinfected WT mice ( Figure 5A).…”
Section: Asc Inflammasome Contributes To Decreased Bacterial Clearancmentioning
confidence: 99%
“…In the academic sector of anti-inflammatory and anti-viral pharmacology, the NLRP3 inflammasome and NF-kB signaling both play essential role in the excessive inflammatory response stimulated by various types of viruses, including RSV, and are closely related to the viral-induced lung injury (Xu et al, 2015;Tate et al, 2016;Chen et al, 2017;Coates et al, 2017;Pinar et al, 2017;Ren et al, 2017;Sarvestani and McAuley, 2017). As for the application of effective treatment strategies against inflammatory response caused by RSV invasion, there has been no research paradigm until now.…”
Section: Introductionmentioning
confidence: 99%